2021
DOI: 10.3390/rs13051040
|View full text |Cite
|
Sign up to set email alerts
|

Applying Close Range Non-Destructive Techniques for the Detection of Conservation Problems in Rock-Carved Cultural Heritage Sites

Abstract: Rock-carved cultural heritage sites are often developed in slopes formed by weak rocks, which due to their peculiar lithological, geotechnical, and morpho-structural features are characterized by excellent carvability, which at the same time makes them prone to weathering, deterioration, and slope instability issues. In this context the use of advanced close-range nondestructive techniques, such as Infrared Thermography (IRT) and Unmanned Aerial vehicle-based Digital Photogrammetry (UAV-DP) can be profitably u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…14a-b), countermeasures to instability within the more gently inclined cliff foot could be a terrace-styled combination of geotechnical installations such as anchoring and Nature-Based Solution (NBS) installations in the form of small rock and/or wood dams in the realms of landscape and cultural compatibility. A system of drainage conduits could prevent uncontrolled infiltration, in particular to the lowest lithological layer, which consists mainly of clay, making it susceptible to swelling phenomena (Frodella et al 2021). NBS could also be adapted for footpaths to ensure safe-yet inoffensive-access to the cliff.…”
Section: Discussion Recommendations and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…14a-b), countermeasures to instability within the more gently inclined cliff foot could be a terrace-styled combination of geotechnical installations such as anchoring and Nature-Based Solution (NBS) installations in the form of small rock and/or wood dams in the realms of landscape and cultural compatibility. A system of drainage conduits could prevent uncontrolled infiltration, in particular to the lowest lithological layer, which consists mainly of clay, making it susceptible to swelling phenomena (Frodella et al 2021). NBS could also be adapted for footpaths to ensure safe-yet inoffensive-access to the cliff.…”
Section: Discussion Recommendations and Perspectivesmentioning
confidence: 99%
“…Furthermore, data from a recently initiated kinematic assessment of fractures, including on-site extensometers (Fig. 15b; Frodella et al 2021), could be included in improved numerical models, as fracture sets are reported not only to be slope-parallel but also to slope-perpendicular and randomly orientated (NACHPG 2019). In this context, the transformation of the continuum into a discontinuum model can be considered.…”
Section: Discussion Recommendations and Perspectivesmentioning
confidence: 99%
“…UAV-DP was used to create a high-resolution 3D model of the investigated rock slope. Digital photogrammetry (DP) is a rapid, efficient, accurate, and safe technique to collect 3D geometric data from stereoscopic overlaps of photo sequences (Frodella et al 2021). In recent years, UAV-based photogrammetric surveys have become increasingly popular in geological studies applied to landscape and environment management (Sturzenegger and Stead 2009).…”
Section: Uav-dp Surveymentioning
confidence: 99%
“…"Closerange" refers to all survey methods implying a camera/ scanner-to-object distance of up to about 300 m (Wolf and Dewitt 2000). Many authors have recognized the potential and advantages of these techniques for rock slope characterization and monitoring in natural and urban environment (Abellán et al 2009;Dotta et al 2017;Fanti et al 2013;Frodella et al 2021;Gigli and Casagli 2011;Gigli et al 2012Gigli et al , 2014aJaboyedoff et al 2008;Sturzenegger and Stead 2009). Also, Borgatti and Tosatti (2010) confirmed the importance of how close-range methods combined with traditional geomechanical characterization could lead to useful methods to assess hazard in rock slope equipped for sport climbing practice.…”
Section: Introductionmentioning
confidence: 99%
“…In other cases, landslides can directly threaten the integrity of sites located in mountainous regions and relatively high relief areas [4][5][6][7]. For this reason, many efforts are being made for developing interdisciplinary approaches devoted to the assessment of landslide hazard in such areas [8][9][10], also through new technologies such as remote sensing techniques [11][12][13][14], with the aim of improving specific management plans [15][16][17]. In this work we analyzed active rockfall processes threatening the Lucus Angitiae archaeological site, which is located north of Luco dei Marsi, a small village in the Apennine region of central Italy (Figure 1).…”
Section: Introductionmentioning
confidence: 99%